Sosialisasi Pengenalan Dasar Komputer dan Internet bagi Komunitas Fixie Purwokerto - Zhafran Mahardika; Muhammad Maulana Alfa Syakan; Rizza Anugrah Khoeron Ni’matulloh; Nanda Agung Setio (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2025)
The development of digital technology today has influenced various aspects of human life, from communication to instant access to information, but the digital literacy gap is still felt by some people, especially in non-technical communities. This community service activity aims to improve basic understanding of computers and the internet for the Purwokerto Fixie Community, a bicycle community whose members come from various ages and educational backgrounds. The socialization method is carried out interactively with a simple language approach, so that the material can be optimally absorbed by participants who have minimal digital experience. The material presented includes an introduction to computer devices, basic concepts of internet networks, digital security, and an understanding of the latest technologies such as 5G and the Internet of Things (IoT). The evaluation results showed an increase in participants' knowledge of basic digital literacy, as well as an awareness of the importance of using information technology safely and responsibly. This activity is the first step in efforts to empower communities through increasing inclusive and applicable digital literacy.